Power station remote monitering system based on thing networking - Li Ping; Yang Wenjun; Yan Huiqin (2016)
The utility model discloses a power station remote monitering system based on thing networking, including intelligent mobile device, PC, database server, GPRS wireless controller, data collection station and gen -set, intelligent mobile device with the PC communication is connected, the PC with the database server communication is connected, database server with data collection station connects GPRS wireless controller is last, gen -set connects data collection station. The utility model discloses a data collection station monitors this fixed equipment of generator, saves into data service ware with monitoring results through GRPS wireless controller to obtain the monitoring data, in time report to the police and carry out system management by the PC. Overall structure is simple, operation convenient to use. 本实用新型公开了种基于物联网的水电站远程监控系统，包括智能移动设备、PC机、数据库服务器、GPRS无线控制器、数据采集器与发电机设备；所述智能移动设备与所述PC机通讯连接；所述PC机与所述数据库服务器通讯连接；所述数据库服务器和所述数据采集器都连接在所述GPRS无线控制器上；所述发电机设备连接所述数据采集器。本实用新型采用数据采集器对发电机这固定设备进行监测，将监测结果通过GRPS无线控制器存储进数据服务